Analisis Metode Guru Dalam Meningkatkan Kemampuan Mengenal Huruf Abjad Pada Anak Usia Dini - Sela Salsabila; R Agustinus Arum Eka Nugroho (Universitas Hamzanwadi, 2026)
Children's development greatly benefits from the ability to recognize the alphabet because it helps them prepare to become readers. The purpose of this study was to gain an in-depth understanding of the emerging phenomenon in the field regarding the role of teachers in helping young children recognize letters. To collect data for this study, researchers used a qualitative research strategy, involving the collection of information from various sources, including journals, articles, interviews, direct observations, and field observations. Based on the research findings, teachers use various techniques to help young students learn to recognize letters. These techniques include phenotypic approaches, visual methods, and kinesthetic methods. Visual methods, which involve the use of letter cards or digital media, have made it easier for children to recognize letters and become more engaged in learning. However, some children still cannot distinguish letters, and teachers have noticed this has been happening since the beginning of the school year or after the lesson. The root of the problem is a lack of experience memorizing letters before entering school. Because it is so important for children's learning process, parents and the surrounding community also assist teachers.